A pilot study on the association between SLCO1B1 RS4363657 polymorphism and muscle adverse events in adults with newly diagnosed dyslipidaemia who were prescribed a statin: the Malaysian primary health care cohort. (3rd October 2019) - C. Thambiah, Subashini; Meor Anuar Shuhaili, Meor Fairuz Rizal; Chew, Boon How; Samsudin, Intan Nureslyna; Abdul Rahman, Hejar; Stanslas, Johnson; Hasan, Shariful; Ahmad, Zalinah
Abstract: Introduction: Statin, the first-line treatment for dyslipidaemia, may have suboptimal adherence due to its associated muscle adverse events. These data, however, remain limited. Aim: To determine the association of serum creatine kinase (CK) and SLCO1B1 rs4363657 polymorphism with statin-associated muscle adverse events (SAMAE) among dyslipidaemia participants. Methods: This was a prospective cohort study at government health clinics involving newly diagnosed adults with dyslipidaemia. SAMAE were recorded based on the patient's complaint after a month on statin. CK was taken at baseline and follow-up. Genetic profiling was performed for SLCO1B1 rs4363657 polymorphism. Results: Among 118 participants, majority were Malay (72%) males (61%) with a mean age of 49 ± 12.2 years old and prescribed lovastatin (61.9). There was a significant association between statin types (lovastatin and simvastatin) and SAMAE ( p = 0.0327); no significant association noted between CK and SAMAE ( p = 0.5637). The SLCO1B1 rs4363657 polymorphism was significantly associated SAMAE ( p < 0.0001). Conclusions: In this first pilot study of a multiethnic Malaysian population, the incidence of SAMAE was 18.6%. SAMAE were significantly higher in subjects on lovastatin compared to simvastatin. SLCO1B1 rs4363657 polymorphism was a significant risk factor for SAMAE.